Antibiotic Resistance Patterns in Gram-Negative Bacterial Infections Among Pediatric Patients: A Cross-Sectional Study at a Tertiary Care Hospital - Nida Imdad, Anwaar Khurshid, Muhammad Awais Mahmood, Madeeha Aimen, Mahwish Ashraf, Ahsan Idrees, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gram-negative bacterial infections are a major cause of morbidity and mortality among pediatric patients, with rising antimicrobial resistance further complicating treatment. Objective: This study assessed the prevalence, resistance patterns, and clinical outcomes of gram-negative infections in children. Methods: This was a cross-sectional observational study conducted at Children Hospital, Faisalabad from December 2022 to May 2023, including a total of 220 pediatric patients diagnosed with gram-negative bacterial infections. Clinical and demographic information was recorded for each patient, including age, gender, admission unit (ward/NICU/PICU), and suspected infection site. Specimens such as blood, urine, cerebrospinal fluid, tracheal aspirates, wound swabs, and sputum were collected under aseptic conditions and sent to the microbiology laboratory for processing. Results: The mean age of the cohort was 3.2 ± 3.8 years, with NICU/PICU patients significantly younger (1.1 ± 1.4 years) than ward patients (5.3 ± 4.2 years, p < 0.001). E. coli was the most common organism (38.6%), while Pseudomonas and Acinetobacter were more prevalent in NICU/PICU (20.0% and 16.3%). Resistance to third-generation cephalosporins (68.2%), fluoroquinolones (52.7%), and carbapenems (18.6%) was high, with significantly higher resistance in NICU/PICU patients (p < 0.05). ESBL-producing strains accounted for 41.8%, MDR for 37.2%, and carbapenem-resistant isolates for 18.6%, with all resistance types significantly more common in critically ill patients. NICU/PICU children had significantly worse outcomes, including higher rates of mechanical ventilation (32.7%), septic shock (21.8%), prolonged hospital stay (50.9%), and mortality (13.6%). Conclusion: Gram-negative infections in pediatric patients exhibit alarming levels of antimicrobial resistance, especially in critically ill children. The high prevalence of MDR, ESBL, and carbapenem resistance underscores the need for strengthened antibiotic stewardship, improved infection-control strategies, and ongoing surveillance to ensure effective treatment outcomes. Keywords: Gram-negative bacteria, pediatric infections, antibiotic resistance, MDR, ESBL, carbapenem resistance